Impact of Cooking Processes on Volatile Flavor Compounds and Free Amino Acids in Fish Sauce - Jin-Xiu Xu; Xin Zhang; Bai-Feng Fu; Xin-Yu Qiao; Zhen-Yu Wang; Xian-Bing Xu; Shu-Zhen Cheng; Ming Du (Foods)
Fish sauce is a widely used condiment in cooking. However, the effects of various cooking processes on its quality remain poorly understood. This study evaluated the quality of fish sauce subjected to various cooking methods (boiling for 10, 30, and 60 min and stir-frying for 10, 30, and 60 s) using sensory evaluation, electronic nose, gas chromatography-mass spectrometry, and free amino acid analysis. Thermal cooking processes significantly altered the flavor profile of the fish sauce. A total of 38 volatile compounds were identified and quantified, 10 of which were screened as key aroma-active compounds based on their high odor activity values (OAVs ≥ 1). The total OAV values of key flavor compounds were lowest in unheated fish sauce (346.51) and varied from 347.64 to 707.40 in heated fish sauce. The maximum total free amino acid contents in boiled and stir-fried fish sauce were 4862.52 mg/100 mL and 4922.49 mg/100 mL, respectively, which were significantly higher than those in unheated fish sauce (4577.54 mg/100 mL) (p < 0.05). Pearson correlation analysis indicated that temperature modulates the production of key flavor compounds in fish sauce by influencing amino acid metabolism. These findings provide valuable insights into the application of fish sauce in food production and culinary practices.